Specific Learning Disorder in Elementary School Students: A Systematic Review - Dewi Kapita Sari; Antonius Totok Priyadi; Siti Halidjah (Celebes Journal of Elementary Education, 2026)
Specific Learning Disorder (SLD) is a neurocognitive disorder affecting 5–15% of elementary students, with dyslexia being the most prevalent form, particularly in boys. This systematic review, following PRISMA guidelines, synthesized 22 articles from PubMed and Scopus to examine SLD prevalence, influencing factors, comorbidities, and effective interventions. Key findings indicate SLD stems from deficits in executive function, working memory, genetic factors, and maladaptive learning environments. Children with SLD face high risks of comorbidities like anxiety (21%), depression (28%), ADHD (28%), and behavioral disorders (22%). Effective interventions identified include cognitive rehabilitation, multisensory teaching methods, and specific technological approaches: eye-tracking applications for early dyslexia screening (e.g., tablet-based tools achieving 84,62% accuracy), the Lexia® Core5® reading edtech program improving academic outcomes, and NAO robots showing efficacy comparable to standard human tutoring. The review concludes that early screening, holistic interventions combining cognitive and technological strategies, and robust family-teacher collaboration are vital for optimizing the academic and psychological well-being of children with SLD. This synthesis provides an evidence-based foundation for policymakers, educators, and researchers designing targeted support systems.